(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Vocabulary is a fundamental component of language learning, especially for young learners. Vocabulary serves as the core foundation for the development of the other four critical language skills: reading, listening, speaking, and writing. This article explores interactive methods for teaching English vocabulary to primary students, examining their implementation both in theory and practice. It further examines the role of vocabulary in early language development, reviews relevant literature, and introduces activities successfully implemented in class, specifically tailored for third graders. Drawing on this literature, the article highlights that primary school students typically acquire new words through multisensory engagement (seeing, hearing, and drawing pictures), emphasizing, above all, the critical significance of context.